Structure and Electrochemical Behavior of ZnLaFeO4 Alloy as a Negative Electrode in Ni-MH Batteries - Houyem Gharbi; Wissem Zayani; Youssef Dabaki; Chokri Khaldi; Omar ElKedim; Nouredine Fenineche; Jilani Lamloumi (Energies, 2025)
This study focuses on the structural and electrochemical behavior of the compound ZnLaFeO4 as a negative electrode material for nickel–metal hydride (Ni-MH) batteries. The material was synthesized by a sol–gel hydrothermal method to assess the influence of lanthanum doping on the ZnFe2O4 spinel structure. X-ray diffraction revealed the formation of a dominant LaFeO3 perovskite phase, with ZnFe2O4 and La2O3 as secondary phases. SEM analysis showed agglomerated grains with an irregular morphology. Electrochemical characterization at room temperature and a discharge rate of C/10 (full charge in 10 h) revealed a maximum discharge capacity of 106 mAhg−1. Although La3+ doping modified the microstructure and slowed the activation process, the electrode exhibited stable cycling with moderate polarization behavior. The decrease in capacity during cycling is due mainly to higher internal resistance. These results highlight the potential and limitations of La-doped spinel ferrites as alternative negative electrodes for Ni-MH systems.